Peranan Kreativitas dan Inovasi dalam Peningkatan Produktivitas UMKM Pengolah Mangga Podang (Studi pada Kelompok Tani Wanita â€œBudidayaâ€ Desa Tiron Kecamatan Banyakan Kabupaten Kediri) - Purwaning Diah, Martina (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Kediri Regency is a podang mango center in East Java. Tiron village located on the slopes of Wilis mountain is one of the largest areas of podang mango. It was utilized by local communities to make fresh podang mango into products that have high economic selling value. The womenâ€™s farmer group